Analysis of Saharan Desert dust transport to the Anatolian Peninsula: a megacity perspective - Akınç, Gül. (Thesis (M.S.)-Bogazici University. Institute of Environmental Sciences, 2010., 2010)
Mineral dust is one of the most significant constituent among the air pollutants. Besides its negative effects on human health, it influences the radiation balance of the Earth. The greatest source of mineral dust over the world is known as the Saharan Desert. The lifted dust from the Saharan region has been distributed over many parts of the Northern Hemisphere. Especially, during the spring period, the desert dust has been transported to the eastern Mediterranean region. From this point of view, contribution of Saharan Desert dust to the Istanbul’s coarse particulate matter levels has been investigated. To find out the clues of the transport, a numerical meteorological model called Weather Research and Forecasting has been run for the month of April in year 2008. The meteorological patterns of the model domain such as distribution of horizontal and vertical wind vectors, backward trajectory analysis of Istanbul have been examined to decide on the transport. In addition to the WRF model outputs, three additional models have been used to support the model data. Results of WRF and the other supportive models indicate that during the spring, there is an obvious contribution of Saharan Desert dust to the high PM10 levels of Istanbul.|Keywords: Meteorological Modeling, Saharan Dust Transport, Anatolian Peninsula, Istanbul, WRF.
Keywords: Mineral dusts.; Air -- Pollution.